2016
DOI: 10.1038/srep38953
|View full text |Cite
|
Sign up to set email alerts
|

Meteorite Impact-Induced Rapid NH3 Production on Early Earth: Ab Initio Molecular Dynamics Simulation

Abstract: NH3 is an essential molecule as a nitrogen source for prebiotic amino acid syntheses such as the Strecker reaction. Previous shock experiments demonstrated that meteorite impacts on ancient oceans would have provided a considerable amount of NH3 from atmospheric N2 and oceanic H2O through reduction by meteoritic iron. However, specific production mechanisms remain unclear, and impact velocities employed in the experiments were substantially lower than typical impact velocities of meteorites on the early Earth.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 67 publications
2
24
0
1
Order By: Relevance
“…We used a system consisting of a Fe 36 slab, 16 N 2 , and 38 H 2 O molecules (a total of 182 atoms; see Fig. 1(a)), which is the same one as in our previous study, 12 where the ratio of Fe atoms, N atoms, and H 2 O molecules nearly coincided with that in the experimental starting material. 10 This system represents the initial reactions when a meteorite (the Fe 36 slab) with adsorbed atmospheric N 2 collides with the sea surface while engulfing other atmospheric N 2 .…”
Section: Methods Of Calculationmentioning
confidence: 99%
See 2 more Smart Citations
“…We used a system consisting of a Fe 36 slab, 16 N 2 , and 38 H 2 O molecules (a total of 182 atoms; see Fig. 1(a)), which is the same one as in our previous study, 12 where the ratio of Fe atoms, N atoms, and H 2 O molecules nearly coincided with that in the experimental starting material. 10 This system represents the initial reactions when a meteorite (the Fe 36 slab) with adsorbed atmospheric N 2 collides with the sea surface while engulfing other atmospheric N 2 .…”
Section: Methods Of Calculationmentioning
confidence: 99%
“…In contrast, the temperature rapidly increased at around 0.2 ps, and subsequently it gradually increased from around 2,450 to 3,180 K. This indicates that some exothermic reactions occur. For comparison, the values of the volume ratio, pressure, particle velocity, and temperature at 4 ps in the 5 km/s shock-wave simulation 12 were 0.58, 27.6 GPa, 2.30 km/s, and 2,100 K, respectively. Due to the higher compression ratio (V /V 0 = 0.50 < 0.58), P, U p , and T of the present simulation were greater than those of the previous one.…”
Section: Time Evolution Of Physical Quantitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…A meteorite impact causes chemical interactions within the meteoritic material. Previous experimental and theoretical works have reported that these chemical interactions cause the production of volatiles, organic, and inorganic molecules in simulated impact conditions (Fegley et al, 1986;Mukhin et al, 1989;Sekine et al, 2003;Schaefer and Fegley, 2010;Furukawa et al, 2015;Shimamura et al, 2016). These impact events are the only known unique extraterrestrial event that disrupts an ecosystem in time and space (Cockell and Lee, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…A meteorite impact on planetary surfaces causes a sudden increase in pressure and temperature and generates shock waves (Shimamura et al, 2016). A meteorite impact causes chemical interactions within the meteoritic material.…”
Section: Introductionmentioning
confidence: 99%